Guidelines for the management and treatment of periodic fever syndromes: Periodic fever, aphthous stomatitis, pharyngitis and adenitis syndrome - Terreri, Maria Teresa R.A.; Bernardo, Wanderley Marques; Len, Claudio Arnaldo; da Silva, Clovis Artur Almeida; de Magalhães, Cristina Medeiros Ribeiro; Sacchetti, Silvana B.; Ferriani, Virgínia Paes Leme; Piotto, Daniela Gerent Petry; Cavalcanti, André de Souza; de Moraes, Ana Júlia Pantoja; Sztajnbok, Flavio Roberto; de Oliveira, Sheila Knupp Feitosa; et al. (Elsevier, 2016)
Objective: To establish guidelines based on scientific evidence for the management of periodic fever, aphthous stomatitis, pharyngitis and adenitis (PFAPA) syndrome. Description of the evidence collection method: The Guideline was prepared from 5 clinical questions that were structured through PICO (Patient, Intervention or indicator, Comparisonand Outcome), to search in key primary scientific information databases. After defining thepotential studies to support the recommendations, these were graduated considering theirstrength of evidence and grade of recommendation. Results: 806 articles were retrieved and evaluated by title and abstract; from these, 32 articleswere selected to support the recommendations. Recommendations: 1. PFAPA is a diagnosis of exclusion established on clinical grounds, and one must suspect of this problem in children with recurrent and periodic febrile episodes of unknown origin, or with recurrent tonsillitis interspersed with asymptomatic periods, especially in children in good general condition and with preservation of weight and height development. 2. Laboratory findings are nonspecific. Additional tests do not reveal pathognomonic changes. 3. The evidence supporting an indication for surgical treatment (tonsillectomy with or without adenoidectomy), is based on two non-blinded randomized clinical trials with small numbers of patients. 4. The use of prednisone at the onset of fever in patients with PFAPA proved to be an effective strategy. There is still need for more qualified evidence to support its use in patients with PFAPA. 5. Despite promising results obtained in studies with IL-1β inhibitors, such studies are limited to a few case reports.
Keywords: Aphthous stomatitis; Autoinflammatory syndromes; Cervical adenitis; Childhood; Fever; Guidelines; Pharyngitis; Syndrome of periodic fever